Textile Dye Treated Photoelectrolytically and Monitored by Winogradsky Columns - de Sousa, Mariana Lopes [UNESP]; de Moraes, Peterson Bueno; Matos Lopes, Paulo Renato [UNESP]; Montagnolli, Renato Nallin [UNESP]; de Angelis, Dejanira de Franceschi [UNESP]; Bidoia, Ederio Dino [UNESP] (Mary Ann Liebert, Inc., 2012)
Due to large amounts of wastewater generated by textile industry, studies on degradation and subsequent impact of these effluents are needed when they are released into water bodies. Since reactive dyes present higher degradation when treated by physical and chemical processes, a photoelectrolytic process was used. Ecotoxicological analysis of simulated textile effluents was conducted before and after treatment. Winogradsky columns were used, simulating a microecosystem where algae growth was examined. Results indicated that the photoelectrolytic process achieved satisfactory results in color degradation of the studied dye (Remazol red brilliant), but after 30 min of treatment, even though the effluent became colorless, it reduced dramatically microalgae diversity. Although complete color removal (97%) was not observed, the effluent treated for 5 min did not affect microalgae growth in the same way as the effluent treated for 30 min. An optimum treatment time of 5 min was determined.
Keywords: algae; photoelectrolytic system; remazol red brilliant; winogradsly columns